Internationalization Strategy as Sustainable Governance: Navigating ESG and AI Transformation - Chytilova, Helena (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
Internationalization in higher education is increasingly becoming a component of sustainable university governance in a period of rapid technological, societal, and geopolitical transformation. Rather than being understood primarily through mobility and partnership expansion, it needs to be approached as a strategic and value-based domain of institutional management. Internationalization is shaped not only by new globalization pressures, but also by European Union priorities, transnational project cooperation, sustainability expectations, and AI-driven digital transformation. These developments point to a broader shift from activity-based understandings of internationalization to governance-based approaches. Particular attention is given to more inclusive, equitable, environmentally responsible, and strategically coordinated forms of international engagement through alliances, as well as to the opportunities and governance risks associated with digitalization and artificial intelligence. The changing role of international offices is examined in this context through a brief practice-based reflection, highlighting their repositioning from administrative support units to strategic actors contributing to sustainable institutional development.